Implementasi Etnomatematika Geometri Budaya Lokal dalam Menumbuhkan Karakter Nasionalis Siswa - Hesti Yunitiara Rizqi; Anni Malihatul Hawa (Jurnal Pengabdian Masyarakat (abdira), 2022)
A strategy that can make it easier for students to solve math problems while at the same time growing student character values during the covid-19 pandemic is ethnomathematics. Ethnomathematical learning is a process of assimilation of a culture with mathematics where learning during a pandemic uses zoom meetings and whatsapp groups. There are many cultures that exist in Indonesia that can be applied to geometric mathematics learning, including the shape of traditional houses, motifs on traditional clothing, forms of music, and forms of food typical of each region in Indonesia. The purpose of this community service is that the community service team provides introductions and strategies through ethnomathematical learning of local culture geometry. The implementation of this community service uses the webinar method at the Ngudi Waluyo University PGSD Study Program Office. The application of ethnomathematics in growing students' nationalist character values and webinar activities was declared to meet the indicators of success. The ethnomathematical material presented has provided benefits to community service participants. This material can be used as a guide for participants to develop an ethnomathematics-based mathematics curriculum.